Optimalisasi Laba dengan Menggunakan Metode Simpleks (Studi Kasus: Umkm Pangsit Jebew Rayika) - Moch Salman Sawaludin; Sashi Annisa Yahya; Nabilah Meisya Maulana; Somadi Somadi (CV. Denasya Smart Publisher, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in economic development. However, many MSMEs still determine production quantities based on experience, resulting in inefficient utilization of available resources. This condition also occurs at UMKM Pangsit Jebew Rayika, where production planning has not been based on quantitative analysis despite the high demand for its products. The main limitation faced by the business is the availability of 800 grams of meat and 300 sheets of wonton wrappers per day, which directly affects production capacity. This study applies the Simplex Method in a Linear Programming model to determine the optimal production combination that maximizes profit under these resource constraints. The analysis shows that the optimal production plan is 56.5217 portions of Pangsit Jebew and 4.3478 portions of Pangsit Goreng, generating a maximum daily profit of IDR 110,434.7826 while satisfying all production constraints. The results indicate that the Simplex Method provides an objective approach for determining optimal production decisions and supports more efficient utilization of limited raw materials in MSMEs.